Tungsten/Platinum Hybrid Nanowire Growth via Field Emission Using Nanorobotic Manipulation - Zhan Yang; Masahiro Nakajima; Yasuhito Ode; Toshio Fukuda (Journal of Nanotechnology)
This paper reports tungsten-platinum hybrid nanowire growth via field emission, based on nanorobotic manipulation within a field emission scanning electron microscope (FESEM). A multiwalled carbon nanotube (MWCNT) was used as the emitter, and a tungsten probe was used as the anode at the counterposition, by way of nanomanipulation. By independently employing trimethylcyclopentadienyl platinum (CpPtMe3) and tungsten hexacarbonyl (W(CO)6) as precursors, the platinum nanowire grew on the tip of the MWCNT emitter. Tungsten nanowires then grew on the tip of the platinum nanowire. The hybrid nanowire length wascontrolled by nanomanipulation. Their purity was evaluated using energy-dispersive X-ray spectroscopy (EDS). Thus, it is possible to fabricate various metallic hybrid nanowires by changing the precursor materials. Hybrid nanowires have various applications in nanoelectronics, nanosensor devices, and nanomechanical systems.